Local government and coastal damage: confusion, potential and dreams. Issue 1 (12th July 2019) - Kelly, Andrew H.; Brown, Jasper; Strickland, Aaron
Abstract : Purpose: This paper aims to not only disentangle the recently altered law and policy on coastal management in New South Wales (NSW), Australia, but also raise opportunities for fresh ideas to develop when dealing with both existing and future coastal damage. The focus is on the role of local government which is not only closer to concerned citizens but also faces costal damage on its own doorstep. Design/methodology/approach: The paper explores the topic from the beginnings of relevant statutory law to the current situation, supported by a case study. It is transdisciplinary in nature, encompassing land use and coastal legislation. Findings: The narrative encourages further attention to the key issues at the local level. This is underpinned by the need for planners to move beyond zoning and other restrictive mechanisms to more strategic approaches. All levels of government must recognise that regulatory planning on its own is insufficient. This leads to the need for champions to consider opportunities beyond the ordinary. Originality/value: While this paper will add to a growing literature on coastal damage and action at the local level, its emphasis on the benefits and limitations of the changing statutory system will assist not only policy makers but professional officers at the local forefront.